Vibration Control Systems for Sensitive Equipment: Limiting Performance and Optimal Design - V.M. Ryaboy (Shock and Vibration)
As vibration control requirements become increasingly stringent, designers and users of vibration control equipment turn to devices and systems combining various physical mechanisms. Subsystems based on different physical effects can be combined to achieve the optimal performance for the application. Building an optimal product line that would cover a wide field of applications by combining several products, as opposed to creating one optimal device for a particular application, presents an optimum vibration control problem. This paper reviews optimum vibration control problems based on the idea of limiting performance, and discusses recent development of vibration control devices.